2021
DOI: 10.31729/jnma.6008
|View full text |Cite
|
Sign up to set email alerts
|

Advance Age Pregnancy in a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Women who conceive at advance age are at risk of pregnancy complications and adverse foetal outcome. This study aims to find out the prevalence of pregnancy at advance age in a teaching hospital. Methods: A descriptive cross-sectional study was conducted between October 2019 to August 2020 at department of obstetrics and gynaecology of a tertiary care centre of Nepal, after obtaining ethical clearance from Institutional Review Committee (dated 03/09/2019 with ref no. 266) and informed consent fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The prevalence of AMA women (18.95%) in the present studied Meitei population is in trend with the studies reported from South-East Asian countries. Moreover, a high frequency of very advanced maternal age mothers (≥40 years) is also evidenced in different studies (Mahato et al, 2021;Rajput et al, 2018). The present study also witnesses a high prevalence of very advanced maternal age women (11.80%), and it could be linked to the mother's educational status, as evident from different studies claiming an association between extended women's education and delaying in childbearing age (Carolan, 2003).…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of AMA women (18.95%) in the present studied Meitei population is in trend with the studies reported from South-East Asian countries. Moreover, a high frequency of very advanced maternal age mothers (≥40 years) is also evidenced in different studies (Mahato et al, 2021;Rajput et al, 2018). The present study also witnesses a high prevalence of very advanced maternal age women (11.80%), and it could be linked to the mother's educational status, as evident from different studies claiming an association between extended women's education and delaying in childbearing age (Carolan, 2003).…”
Section: Discussionsupporting
confidence: 77%
“…A study from tertiary centre of Nepal revealed the prevalence of AMA pregnancy was 5.3%. 23 On a global level, a study done in 29 countries (Africa, Asia, Middle East and Latin America) revealed that the magnitude of pregnant women with advanced maternal age was 12.3%. 24 In our study, the prevalence of caesarian section (CS) was 12.8%.…”
Section: Discussionmentioning
confidence: 99%
“…It includes the utilization of methods and systems that diminish agony, nervousness, and injury during medical treatments (Wong et al, 2003). So, the fundamental principles of atraumatic care involve reducing or preventing a child's separation from the family, fostering a sense of control, and minimizing physical harm or discomfort (Mahato et al, 2022).…”
Section: Introductionmentioning
confidence: 99%